2019
DOI: 10.4103/ijn.ijn_242_18
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in peritoneal dialysis patients: Association with the dialysis adequacy and technique survival

Abstract: Introduction:Increased oxidative stress is suggested as one of the possible mechanisms of structural and functional damage to the peritoneal membrane in peritoneal dialysis patients. But there are few available data on the association of oxidative stress with peritoneal dialysis adequacy and technique survival. The present study was undertaken to investigate the association of oxidative stress biomarkers with the peritoneal dialysis adequacy and technique survival.Methods:This prospective single-center observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
8
0
4
Order By: Relevance
“…In our study, we found increased levels of LPO in all types of PT (48) and no correlation with the value of PET. Stepanova et al previously reported the association of MDA with some PD parameters, they also found no correlation with D/P creatinine ratio but a negatively correlation with total KT/V (49).…”
Section: Discussionmentioning
confidence: 89%
“…In our study, we found increased levels of LPO in all types of PT (48) and no correlation with the value of PET. Stepanova et al previously reported the association of MDA with some PD parameters, they also found no correlation with D/P creatinine ratio but a negatively correlation with total KT/V (49).…”
Section: Discussionmentioning
confidence: 89%
“…Thiol compounds are the natural reservoir of the reductive capacity of the cells [29]. Chronic renal failure and CKD are accompanied by disturbances in the redox status of plasma thiols [30]. The results showed that the SH-groups in the blood of patients with CKD I-V stages decreased almost two fold compared to conventionally healthy subjects (Table).…”
Section: Indicatorsmentioning
confidence: 99%
“…Як відомо, дисліпідемія та ОС є одними з важливих механізмів та загальною рисою, що лежать в основі патогенезу ХХН [25][26][27]. Антиоксидант- [6,28].…”
Section: Original Papersunclassified